The Effect of Central Bank Policy Decisions on Stock Market Returns in Chile (2015)
This paper analyzes the stock-market response to monetary policy decisions made by the Central Bank of Chile -- We use a methodology designed for the study of low frequency events and monthly data from September 2001 to December 2013 to estimate the effect of anticipated and unanticipated changes in the Chilean monetary policy interest rate on stock returns -- In contrast to the research findings in the literature for the U.S., we find no evidence that monetary surprises affect Chilean stock returns